DETERMINAN EFISIENSI PERBANKAN DI INDONESIA BERDASARKAN DATA ENVELOPMENT ANALYIS (DEA) - Gracia Masita; Imam Subekti (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to investigate technical efficiency score of banks in Indonesia and examine its determinants i.e. foreign ownership, capital adequacy ratio, non-performing loan and size. Research samples were 53 foreign exchange banks that operated in Indonesia from 2010 until 2012. This research used Data Envelopment Analysis (DEA) to measure efficiency score. The result reveals that scores of technical efficiency show an increasing trend over 2010-2012. Another results shows larger banks can achieve more efficiency. Also, management of non-performing loan is an important factor in improving bank efficiency. On the contrary, foreign ownership of bank and capital adequacy ratio are not able to improve the efficiency in Indonesian banks.   Keywords: Data Envelopment Analysis, Technical Efficiency, Foreign Ownership, Capital Adequacy Ratio, Non-Performing Loan, and Bank Size.